New Approach for Photovoltaic Parameters Extraction for Low-Cost Electronic Devices - Andrés Firman; Cesar Prieb; Alexis Raúl González Mayans; Manuel Cáceres; Luis Horacio Vera; Juan de la Casa Higueras (Energies, 2023)
This work proposes a new five-parameter model equation for PV devices, which operates as a function of the main representative parameters of PV devices. It is specifically developed for implementation in embedded systems. The methodology presented in this work is notable due to the fact that three of the five parameters can be directly extracted from the experimental current–voltage (I–V) curve, simplifying the iterative process until a pre-set small difference in the determination of the maximum power is achieved. The iterative methodology for extracting the remaining parameters is also described. The proposed methodology is verified by applying it to seven different PV technologies, including crystalline and thin-film technologies. Its parameters are compared with those obtained using the highly precise trust region iterative method. The resulting parameters and the error in the adjustment along the I–V curve are discussed. This methodology demonstrates the capability to accurately adjust the model along the entire I–V curve, determine the maximum power, and is not dependent on highly variable parameters.